Gaya Komunikasi Politik Presiden Joko Widodo dalam Menyikapi Isu-Isu Kebijakan Publik Melalui Media Massa - M. Tinov; Baskoro Wicaksono (Nakhoda: Jurnal Ilmu Pemerintahan, 2015)
Every president has a different style of political communication between another. Typology political communication style that uses high political communication context and low context of political communication. President SBY is one president who uses high-context communication while President Jokowi using low context communication, in which the language used is easy to understand, straightforward and not winged so as to avoid different interpretations. President Jokowi communication style in addressing issues of public policy in the mass media is not different when conducting a press conference, the "main shoot straight". Similarly, ministers, causing a political uproar because not coherent between the president and his aides. This study contains the formulation of the problem as follows; First, what are the public policy issues are addressed by the President Joko Widodo in the mass media. Secondly, how political communication styles President Joko Widodo in addressing public issues through the mass media? This study used a qualitative approach and type of penelitain descriptive research strategy research library. Data retrieval technique using 1 (one) way, the documentation of the various mass media, both print and online. This study shows there are 2 (two) typology distribution policy issues regarding the administration of President Jokowi, namely (a) issues into tranding topic in the online media and social media, (b) issues popular in audience the general public as much 12 (twelve) policy issues. Furthermore, political communication Jokowi not managed properly, often a difference between the president and his aides. Therefore Jokowi form of political communication team in charge of providing information to the public. Political communication style is low context cultures adjust communication society because it is influenced by tradition and Mataraman Culture.